Inhibition Predicts the Course of Depression and Anxiety Symptoms Among Adolescents: The Moderating Role of Familial Risk. Issue 2 (24th February 2023) - Stevens, Elizabeth S.; Funkhouser, Carter J.; Auerbach, Randy P.; Talati, Ardesheer; Gameroff, Marc G.; Posner, Jonathan E.; Weissman, Myrna M.; Shankman, Stewart A.
Abstract: Numerous theoretical models suggest that inhibition difficulties—the inability to moderate automatic responses—contribute to the onset and/or maintenance of internalizing symptoms. Inhibition deficits and internalizing disorders run in families and share overlapping genetic risk factors, suggesting that inhibition deficits may be particularly prognostic of internalizing symptoms in those with high familial risk. This study tested this hypothesis in a longitudinal sample during the transition from adolescence to early adulthood. As hypothesized, prospective associations between inhibition and anxiety and depressive symptoms 8 years later were moderated by familial risk for depression. Specifically, poorer inhibition prospectively predicted greater anxiety and depressive symptoms in those at high (but not low) familial risk for major depressive disorder. These findings provide preliminary support for impaired inhibition as an indicator of risk for later internalizing symptoms in those at high familial risk.